Synergistic and counteractive effects of Bi-component plasticizers on structure and electric field-induced bending actuation behaviors of poly (vinyl chloride) (PVC) gels. (21st September 2022) - Li, Beibei; Liu, Zhiwei; Liu, Ying Dan; Liang, Yongri
Abstract: Electroactive dielectric polymer gels (DPGs) have important applications in soft robots, wearable electronics, and biomedical devices etc. However, the relationship between structure and electromechanical properties of DPGs have not been fully understood so far. In this work, the effect of the bi-component plasticizers on the structure, mechanical properties, dielectric properties, and electric field induced dynamic bending actuation behaviors of plasticized poly (vinyl chloride) (PVC) gels with free electrodes were investigated using the dibutyl adipate (DBA) as major plasticizer and the branch structured bio-based triethyl 2-acetylcitrate (ATEC) or triethyl citrate (TEC) as minor second plasticizer (30 wt% of bi-component plasticizer). The PVC gel films bend towards the anode side when applied electric field under free electrodes measurement condition. The electric field induced capacitance change of PVC gels was important factor to influence the bending displacement, which were influenced by the interactions between plasticizers and PVC chains in PVC gels. The bending displacement of PVC/DBA/TEC and PVC/DBA/ATEC gels is about 80% and 140% of PVC/DBA at 7.2 kV (corresponding to 180 V/mm of nominal electric field), respectively. The synergistic and counteractive effects of bi-component plasticizers on the bending actuation of PVC gels are mainly attributed to the competition between plasticization effect of PVC and interactions of inter-plasticizers. Our results provide a new insight for the design of high performance electroactive dielectric polymer gel materials. Highlights: Electric field-induced dynamic bending actuation performances of plasticized PVC gels with free electrodes were enhanced by bi-component plasticizer. Competition between interactions of plasticizers and PVC and interactions of inter-plasticizers is key factor to influence the bending actuation of PVC gel. The electric field induced bending of PVC gels was caused by asymmetric charges accumulation on the both surfaces of PVC gel films. Graphical Abstract: Image 1